Bedtime hypertension chronotherapy best reduces cardiovascular disease risk as corroborated by the Hygia Chronotherapy Trial. Rebuttal to European Society of Hypertension officials. (3rd May 2020) - Crespo, Juan J.; Domínguez-Sardiña, Manuel; Otero, Alfonso; Moyá, Ana; Ríos, María T.; Sineiro, Elvira; Castiñeira, María C.; Callejas, Pedro A.; Pousa, Lorenzo; Salgado, José L.; Durán, Carmen; Sánchez, Juan J.; et al.
ABSTRACT: Reinhold Kreutz and colleagues in a recent editorial claim the Hygia Chronotherapy Trial lacks credibility because of deficient methods, thereby dismissing both the plausibility and clinical significance of its reported findings. They misstate and misrepresent crucial information, findings and conclusions unambiguously detailed in the published report of the Hygia Chronotherapy Trial. The purpose of this communication is to provide a complete rebuttal to each and every one of the misleading and scientifically unsupported claims by Kreutz et al. that calls into question their expertise to decry the merits, advantages, limitations and validity of correctly designed and conducted ambulatory blood pressure monitoring-based chronotherapy trials.